ANALISIS PERMASALAHAN GURU DALAM MENGHADAPI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR INKLUSI - Yuliansyah, Arief; Syihabuddin; Maulia Depriya Kembara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the problems faced by teachers in dealing with students with special needs and how to overcome these problems that have been carried out by previous researchers. This research uses the Systematic Literature Review (SLR) method referring to PRISMA (Prefered Reporting Item for Systematic Review and Meta-Analysis) to examine documents from Google Scholar between 2010 and 2024 related to teacher problems in dealing with students with special needs. Documents were obtained using the Publish or Perish journal search application with the keyword teacher problems in dealing with children with special needs. From the search results, 200 journal articles were obtained. From 200 journal articles, 10 articles were selected that were in accordance with the problems of teachers in dealing with students with special needs. The results of the journal analysis found that the problems faced by many teachers are the first difficulty in preparing lesson plans. Teachers have difficulty designing lesson plans due to lack of training in designing lesson plans, secondly teachers have difficulty in choosing the right learning methods because of the changing moods of students with disabilities.Third lack of media and infrastructure to support learning for students with disabilities. Finally, there is a lack of cooperation between teachers, parents, schools, communities and the government in supporting the implementation of learning for children with disabilities in inclusive schools.